Strategic Recruitment and Selection Practices: Enhancing Business Performance in F&B Sector - Rafiqul Bari Lasker; Muhammad Firdaus Bin Muhammad Sabri (JOURNAL OF SOCIETY INNOVATION AND DEVELOPMENT, 2026)
Background of the problem: In Malaysia's fast-changing food and beverage (F&B) industry, good human resource strategies are very important for keeping business performance up even when there aren't enough workers and competition is getting stronger. Purpose: This study investigates the correlation between recruitment and selection practices, particularly internal and external methodologies, and organizational performance in food and beverage establishments situated in SS2, Kelana Jaya. Method: A quantitative methodology was employed to gather data from 175 employers via structured questionnaires. IBM SPSS Statistics version 27 was used for the analysis, which included descriptive statistics, Pearson correlation, and multiple regression techniques. Result: The results show that both internal and external hiring and selection processes are strongly linked to how well a company does. Internal recruitment and selection proved to be the more robust predictor, exhibiting a standardized beta value of 0.421 and a significance level of 0.001. These results highlight the strategic significance of cultivating internal talent to improve operational efficiency and overall performance. Implication: The research enhances the human resource management literature by providing localized insights and recommends that food and beverage companies invest in organized internal mobility programs while preserving robust external recruitment channels to maximize performance.